Estimation of the Sodium Adsorption Ratio (SAR) and SAR-Adjusted Ratio of groundwater in Siret Najem of Kuwayfiyah- North Libya - Imneisi , Idris Basher (Scientific Journal of University of Benghazi, 2022)
The Kuwayfiyah district is located northeast of Benghazi, Libya. It includes some agricultural areas. In this study, an attempt was made to assess the quality of irrigation water in Siret Najem by collecting and identifying water samples to represent the study area from 3 main stations during the month of May 2022. The quality characteristics that were examined in this study were: Total Dissolved Salts (TDS), pH, conductivity, positive ions (K+, Na+, Mg2+, Ca2+), and negative ions (HCO3, Cl-, SO4, and CO3) to estimate the sodium adsorption index (SAR) and the sodium adsorption index (Adjusted). The results in the study area showed a reduced risk of sodium using both the sodium adsorption index (SAR) and the Adjusted sodium absorption index as they were (5.167, 4.54), respectively. However, some of the groundwater samples were observed to be of good quality for irrigation in the study area.